2018
DOI: 10.1111/ffe.12934
|View full text |Cite
|
Sign up to set email alerts
|

A computational strategy for damage‐tolerant design of hollow shafts under mixed‐mode loading condition

Abstract: Three‐dimensional numerical analyses, using the finite element method (FEM), have been adopted to simulate fatigue crack propagation in a hollow cylindrical specimen, under pure axial or combined axial‐torsion loading conditions. Specimens, made of Al alloys B95AT and D16T, have been experimentally tested under pure axial load and combined in‐phase constant amplitude axial and torsional loadings. The stress intensity factors (SIFs) have been calculated, according to the J‐integral approach, along the front of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Whether it is from industrial design thinking or production practice, it has brought new creative space and possibilities, but its research has not revealed the limitations of 3D printing in industrial design. It is not conducive to the final predictive analysis [5].…”
Section: Introductionmentioning
confidence: 99%
“…Whether it is from industrial design thinking or production practice, it has brought new creative space and possibilities, but its research has not revealed the limitations of 3D printing in industrial design. It is not conducive to the final predictive analysis [5].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed different crack propagation mechanisms in notched and unnotched specimens. Citarella et al 18 and Lepore et al 19 investigated the crack propagation of an edge crack in a cylindrical specimen under multiaxial cyclic loading conditions. Nevertheless, the numerical simulation technique adopted in these studies was inefficient in replicating the pure torsion loading condition.…”
Section: Introductionmentioning
confidence: 99%